The History of the Chuvash People through the Eyes of an Ethnographer - Anton K. Salmin (Журнал Фронтирных Исследований)
Ethnic history presupposes an interdisciplinary analysis of primary sources and basic publications on the subject. For this reason, the researcher must possess the skills not only of a historian; he is obliged to include the scholarly achievements in the study of ethnonyms, geography, genetics, anthropology, archeology, religion, ethnography, linguistics, art history, and folklore studies. In this instance, we turn our attention only to several fundamental characteristics and events in the traditional ethnography of the Chuvash people. The article covers the Caucasian, Volga-Don, and Middle Volga stages, according to the historical period in which the ancestors of the Chuvash were living. They are space-time boundaries in the history of the Chuvash. An interdisciplinary approach (history <-> ethnography) is used. The chronology of events extends from the 2nd to 10th centuries. At the same time, we try to trace the historical dynamics of one or another tendency. All of this should further the study of the ethnic history of one of the numerous peoples of the Russian Federation.